Adaptation of Microalgae to Environmental Factors (The Peerian Journal, 2023)
The algal flora of the treatment plant in Namangan city was studied. The study of the floristic composition of the bioponds of the treatment plant showed that species from the genus Chlamydomonas Ehr are dominant. The dominant species and strains of microalgae have been identified and the photosynthetic productivity of representatives of green, blue-green and euglena algae under intensive controlled conditions has been comparatively studied, and the ways of adaptation of individual species and strains to high light and temperature have been clarified